Neuroinvasive Listeria monocytogenes Infection Triggers IFN-Activation of Microglia and Upregulates Microglial miR-155 - Zhang, Miao; Gillaspy, Allison. F.; Gipson, Jenny R.; Cassidy, Benjamin R.; Nave, Jessica L.; Brewer, Misty F.; Stoner, Julie A.; Chen, Jie; Drevets, Douglas A. (Frontiers in Immunology, 2018)
MicroRNA (miR) miR-155 modulates microglial activation and polarization, but its role in activation of microglia during bacterial brain infection is unclear. We studied miR-155 expression in brains of C57BL/6 (B6.WT) mice infected i.p. with the neuro-invasive bacterial pathogen Listeria monocytogenes (L. monocytogenes), then were treated with ampicillin starting 2 days (d) post-infection (p.i.) and analyzed 3d, 7d, and 14d p.i. Virulent L. monocytogenes strains EGD and 10403s upregulated miR-155 in whole brain 7d p.i. whereas infection with avirulent, non-neurotropic hly or actA L. monocytogenes mutants did not. Similarly, infection with virulent but not mutated bacteria upregulated IFN- mRNA in the brain at 7d p.i. Upregulation of miR-155 in microglia was confirmed by qPCR of flow cytometry-sorted CD45intCD11bpos brain cells. Subsequently, brain leukocyte influxes and gene expression in sorted microglia were compared in L. monocytogenes-infected B6.WT and B6.Cg-Mir155tm1.1Rsky/J (B6.miR-155-/-) mice. Brain influxes of Ly-6Chigh monocytes and upregulation of IFN-related genes in microglia were similar to B6.WT mice at 3d p.i. In contrast, by d7 p.i. expressions of microglial IFN-related genes, including markers of M1 polarization, were significantly lower in B6.miR-155-/- mice and by 14d p.i., influxes of activated T-lymphocytes were markedly reduced. Notably, CD45highCD11bpos brain cells from B6.miR-155-/- mice isolated at 7d p.i. expressed 2-fold fewer IFN- transcripts than did cells from B6.WT mice suggesting reduced IFN- stimulation contributed to dampened gene expression in B6.miR-155-/- microglia. Lastly, in vitro stimulation of 7d p.i. brain cells with heat-killed L. monocytogenes induced greater production TNF in B6.miR-155-/- microglia than in B6.WT microglia. Thus, miR-155 affects brain inflammation by multiple mechanisms during neuroinvasive L. monocytogenes infection. Peripheral miR-155 promotes brain inflammation through its required role in optimal development of IFN--secreting lymphocytes that enter the brain and activate microglia. Microglial miR-155 promotes M1 polarization, and also inhibits inflammatory responses to stimulation by heat-killed L. monocytogenes, perhaps by targeting Tab2.